Minocycline plus Zinc Oxide Eugenol Cement Might Be A Promising Alternative for Acute Pulpitis. (9th May 2022) - Song, Hongning; Lei, Yintao; Xing, Zaichen; Liu, Min
Abstract : Objective . To investigate the clinical effect of minocycline plus zinc oxide eugenol cement in the treatment of acute pulpitis and its effect on the levels of HIF-1 α, Bcl-2, and tumor necrosis factor α . Methods . A total of 286 patients with acute pulpitis who were treated in our hospital from January 2019 to October 2020 were recruited and assigned (1 : 1) via random number table method to receive either minocycline (control group) or minocycline plus zinc oxide eugenol cement (study group). Outcome measures included treatment effect, tooth mobility, tooth percussion pain score, hypoxia-inducible factor (HIF)-1 α and B-lymphocyte tumor (Bcl)-2 positive rate, and tumor necrosis factor (TNF- α ). Results . Minocycline plus zinc oxide eugenol cement was associated with significantly lower scores of teeth mobility and percussion pain versus minocycline alone (p < 0.05 ). Minocycline plus zinc oxide eugenol cement resulted in a significantly higher treatment efficacy (97.20%) versus minocycline alone (72.73%) (p < 0.05 ). Minocycline plus zinc oxide eugenol cement was associated with significantly lower positive rates of HIF-1 α and Bcl-2 and lower levels of TNF- α versus minocycline alone (p < 0.05 ). The patients receiving minocycline plus zinc oxide eugenol cement showed significantly lower visual analogue scale (VAS) scores and faster pain relief versus those given minocycline alone (p < 0.05 ). Conclusion . Minocycline plus zinc oxide eugenol cement offers a viable alternative for acute pulpitis as it mitigates the pain of patients, alleviates inflammatory responses, and lowers the positive rate of HIF-1 α and Bcl-2, so it is worthy of clinical promotion.